Houssay phenomenon: a rare case of diabetes mellitus remission - Zhang, JTW; Ho, KWK (International Diabetes Nursing, 2011)
Abstract Hypoglycaemia in a type 2 diabetes patient can be due to oral hypoglycaemic agent(s), in particular sulphonylureas, or insulin therapy. Pituitary dysfunction is a less common, yet important, cause of severe hypoglycaemia. Associated features include nausea, dizziness, hypotension, and hyponatraemia. We describe a case of severe hypoglycaemia in an individual with insulin treated type 2 diabetes, secondary to panhypopituitarism from a Rathke’s cyst. A brief overview on Rathke’s cysts is provided.